The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.7601/mez.61.335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological differences of Haematobia irritans and H. exigua, and molecular phylogeny of Japanese Stomoxyini flies (Diptera, Muscidae)

Abstract: Molecular analysis based on mitochondrial DNA (mtDNA) sequence was performed to elucidate the genetic di#erence between Haematobia irritans (Linnaeus) and H. exigua (de Meijere), and the phylogenetic relationship among Japanese Stomoxyini species (Stomoxys calcitrans (Linnaeus), S. indicus Picard, S. uruma Shinonaga et Kano, and Haematobosca sanguinolenta (Austen) including Haematobia). Two populations obtained from Obihiro and Morioka which were morphologically identified as H. irritans were genetically ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Singh and Achint (2017) found that Musca species formed a sister clade with Haematobia irritans which supports our results. Iwasa and Ishiguro (2010) reported Haematobia and Musca as sister clade similar to our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Singh and Achint (2017) found that Musca species formed a sister clade with Haematobia irritans which supports our results. Iwasa and Ishiguro (2010) reported Haematobia and Musca as sister clade similar to our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Musca species form a sister clade with Haematobia irritans , whereas Stomoxys calcitrans form a different clade. Iwasa and Ishiguro (2010) also reported Haematobia and Musca as sister clade.…”
Section: Discussionmentioning
confidence: 94%
“…Both species have proven to be highly invasive and have often been classified as subspecies . It is hard to discriminate between them morphologically, whereas at the molecular level, ribosomal genes are conserved, and mitochondrial genes have a relatively low divergence of 1.8–1.9% . The estimated cost of HF and BF to cattle production worldwide is more than US $3.6 billion per annum .…”
Section: Introductionmentioning
confidence: 99%